PENGARUH INSTRUMEN MONETER (OPEN MARKET OPERATION, PASAR UANG ANTAR BANK DAN RESERVE REQUIREMENT ) DALAM DUAL MONETERY SYSTEM TERHADAP VOLUME UANG PRIMER DALAM MASA KRISIS DI INDONESIA. - Oke Setiarso (Ilmu Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Unsoed, 2011)
ABSTRACT This research entitled “ The Influence of Monetary Instrument of Dual Monetary System to Base Money Volume In Indonesia “ Result of this research shown that improvement on SBI and GWM position can reduce base money volume.The transaction volume of Conventional Banking money market ( PUAB) can not give contibution to change variation of base money volume, because in Conventional Banking have over liquidity. Meanwhile, the position SWBI,PUAS dan GWMs also cannot give contribution yet to change variation of base money volume. It’s because The Share of sharia Banking is relatively in low level operational. This research implies : The Government is always to maintain a good economy conditions and Indonesian Bank can decrease discount rate to make the Business so investors growth again and Banking System can always to increase Loan to Deposite Ratio Bank . Key words ; Monetary Instrument , Dual Monetary System, Base Money.